Primary hyperparathyroidism in pregnancy: a case report and review of the literature - Li Hao; Yalin Chen; Yumei Lu; Rui Wang (Frontiers in Medicine, 2026)
Primary hyperparathyroidism during pregnancy represents an exceedingly rare clinical entity. Its early manifestations are frequently subtle and easily masked by physiological adaptations of gestation, frequently leading to diagnostic delay. Persistent hypercalcemia carries substantial hazards to both maternal and fetal wellbeing, while relevant clinical literature remains limited. Herein, we present an advanced maternal age patient with recurrent pregnancy loss complicated by second-trimester persistent nausea and vomiting. Serum biochemistry demonstrated marked hypercalcemia and elevated parathyroid hormone, cervical ultrasonography identified a hypoechoic nodule within the right parathyroid gland. The combined biochemical and imaging findings were consistent with pregnancy-associated primary hyperparathyroidism. Following medical correction of hypercalcemia, the patient successfully underwent parathyroidectomy under general anesthesia. However, at 2 months postpartum, she developed acute abdominal pain due to renal calculi and subsequently underwent lithotripsy. In summary, primary hyperparathyroidism in pregnancy is relatively rare, however, vigilant monitoring of serum calcium levels is imperative throughout the gestational period. Management strategies should be individualized based on gestational age and clinical severity to optimize maternal and fetal outcomes. For severe cases requiring surgery, precise preoperative localization of parathyroid lesions is essential. Notably, the second trimester is considered the optimal window for surgical intervention.